Evolutionary Relationship and Structural Characterization of the EPF/EPFL Gene Family - Takata, Naoki; Yokota, Kiyonobu; Ohki, Shinya; Mori, Masashi; Taniguchi, Toru; Kurita, Manabu (PLOS ONE, 2013)
EPF1-EPF2 and EPFL9/Stomagen act antagonistically in regulating leaf stomatal density. The aim of this study was to elucidate the evolutionary functional divergence of EPF/EPFL family genes. Phylogenetic analyses showed that AtEPFL9/Stomagen-like genes are conserved only in vascular plants and are closely related to AtEPF1/EPF2-like genes. Modeling showed that EPF/EPFL peptides share a common 3D structure that is constituted of a scaffold and loop. Molecular dynamics simulation suggested that AtEPF1/EPF2-like peptides form an additional disulfide bond in their loop regions and show greater flexibility in these regions than AtEPFL9/Stomagen-like peptides. This study uncovered the evolutionary relationship and the conformational divergence of proteins encoded by the EPF/EPFL family genes.